Mathematical Reasoning of Junior High School Students in Solving HOTS Problems in Terms of Self-Efficacy - Aura Sya’banningrum; Cholis Sa'dijah; Desi Rahmadani (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to describe the mathematical reasoning of junior high school students in solving HOTS problems in terms of self-efficacy. This research is descriptive research with qualitative approach. This study involved three seventh grade students from a junior high school in Malang City, as research subjects. The data in this study were obtained using instruments, such as mathematical reasoning HOTS test sheet, self-efficacy questionnaire sheets, and interview guideline. Data analysis in this research consists of three stages, namely data reduction, data display, and conclusion drawing/verification. The results of research showed that student with low self-efficacy meets the indicators of reflecting the solution to a problem, while student with high self-efficacy and student with moderate self-efficacy are able to meet all indicators of mathematical reasoning, such as analyzing a problem, implementing strategy, and reflecting on a solution to a problem.